Financial Management Governance Effectivity on Economic Value Added - Ainun Jariah; Hesti Budiwati (LPPM of NAROTAMA UNIVERSITY, 2021)
Objective: is to analyze and get empirical evidence of the effect of investment decisions, funding decisions, dividend policy, good corporate governance and profit management both partially and simultaneously on economic value added. Design/method/approach: the method used is quantitative method with causality, survey and explanatory as well as predictive. The population in this research is manufacturing companies in Indonesia from various sectors of 2013-2017 and based on purposive sampling technique, the sample is 37 companies. Results: the result of the study shows that of the five predictor variables, the dividend policy is the only predictor variable that has effect on economic value added, while simultaneously all predictor variables are not able to affect the economic value added variable. Limitations/research implications: the population of this study is manufacturing companies from various with different industries ratio. Practical implications: to meet the economic value added value, the profit management (income smoothing) does not need to be implemented. For the investors to pay attention to the financial decisions of the companies. Originality/value: is using the profit management, especially income smoothing action as a predictor variable on economic value added. Keywords: Economic Value Added, Good Corporate Governance, Dividend Policy, Investment Decisions, Funding Decisions, Profit Management.